A reprodução do espaço da pequena produção rural familiar em Canguaretama/RN - Marinho, Fábio Daniel Pereira (2009)
This study aimed to explore the process of reproduction of space from the small family farm production in the municipality of Canguaretama, specifically focused on foodstuffs of plant origin, seeking to understand the changes in agrarian space canguaretamense and its impact on small family farms the last 35 years. Since colonization, during the seventeenth century, the production of space agrarian Canguaretama was founded under a structure based on large ownership and cultivation of cane sugar. Secondly, it was being built a small space reserved for food production to meet both the consumption of property, but also for local marketing. In the centuries following the changes in the capitalist system imposed a new dynamic for small food production, mostly in the early twentieth century, with processing plants and mills in the area extending toward the cultivation of sugarcane. In the second half of that century, mainly in the 1980s, the cultivation of cane sugar was encouraged to produce alcohol, which led to a further expansion of sugar cane toward the areas targeted for the production of foodstuffs. Currently, the framework of small food production differs little from the period of colonization in relation to the difficulties faced by this segment of agriculture. Thus, we have a reality based on socio-spatial inequality, and the near absence of the Government, which requires urgent implementation of public policies for the production and organization of small producers into associations or cooperatives to improve the productivity and hence in their standards of living and their families